Interventions to Increase Dairy Consumption in Adolescents: A Systematic Review - Marquez, Olivia; Racey, Megan; Preyde, Michèle; Hendrie, Gilly A.; Newton, Genevieve (Infant, child & adolescent nutrition, 2015)
Objective. Effective interventions are needed to address the reported inadequacies of dairy product and calcium (Ca) intakes among adolescents. The present review investigated interventions aimed at increasing adolescent dairy and/or Ca intakes and determined the characteristics associated with successful interventions. Design. A PRISMA systematic review search identified 17 interventions, described in 16 publications, between 1993 and 2015 (February). Studies were evaluated for population, delivery, dietary targets and outcomes measures, measure of intervention intensity, use of behavior change techniques, intervention effectiveness, and effect size and quality. Setting. Interventions targeting an increase in dairy food or Ca intake, either exclusively or in combination with other dietary modifications. Subjects. Adolescents, aged 12 to 18 years. Results. Twelve of the 17 interventions were found to be effective. Effective interventions tended to be higher in overall intensity (mean intensity: negative interventions 12.2, positive interventions 14.25), with the most notable difference in the duration category, such that effective interventions tended to be longer in duration. The number of behavior change techniques applied did not differentiate effective and ineffective interventions, but prompting the review of behavioral goals and including interviews or brief counseling appeared to be important for effective interventions. Effective interventions tended to have higher methodological quality, while the majority of ineffective interventions were qualitatively assessed as weak. Conclusions. The current review has identified characteristics of effective interventions that offer insight into promising strategies likely to increase dairy consumption and Ca intakes in countries where adolescent intake is insufficient. These findings may have important implications for future intervention design.